Mengembangkan Jiwa Kewirausahaan Sebagai Dasar Menjalankan Usaha - (Jurusan Teknik Mesin Politeknik Negeri Semarang), Nur Saada (Teknis, 2016)
Nowadays more and more members of the public who tried to enter into the world of business, whether micro, small and medium. The intention of entering the business world in general is driven by national economic conditions are not yet fully capable of creating jobs, good for those who at this moment ready to enter the workforce, as well as new labor force, ie those who have recently graduated from an educational institution or caused by various causes can not be forced to complete their education. Those who drop out of school or who are not able to continue to pursue higher education also need to get a decent and dignified life. So in order to survive, they choose the alternative to enter the business world. With capital determination, passion or whatever possessed them to try berwirausaha.Mereka not easily give up the face of lifes difficulties, but among them many of them fail. Studying the failure of these efforts, among others, caused by the perpetrator that are less or not develop the entrepreneurial spirit in running the business.Keywords: Entrepreneurial spirit, running a business